Social Media As A Moderator In The Relationship Between Financial Literacy And Skills Toward Financial Inclusion: An Sem-Based Study On Msmes In Palopo - Syarifuddin, Purnama; Rusli, Andika; Sultan, Sultan (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to analyze the moderating role of social media in the relationship between financial literacy, financial skills, and financial inclusion among MSMEs in Palopo City. Methodology: This research adopts a quantitative approach using a survey method targeting MSME owners in Palopo City. Data were analyzed using descriptive statistics and variance-based Structural Equation Modeling (SEM) with Partial Least Squares (PLS) techniques, utilizing SmartPLS 3 software. Results: The findings indicate that financial literacy, financial skills, and social media usage have a positive and significant effect on financial inclusion. However, social media does not significantly moderate the relationship between financial literacy and financial skills on financial inclusion. Novelty: This study integrates social media as a moderating variable within a financial inclusion framework for MSMEs in a regional Indonesian context. Findings: Financial literacy and financial skills remain the primary determinants of financial inclusion, while social media functions more as a supporting channel rather than an effective moderator. Originality: The originality of this study lies in its empirical evidence on MSMEs in Palopo City, contributing to limited research on digital financial inclusion in secondary urban areas. Conclusions: Improving financial inclusion requires strengthening financial education and financial skills while optimizing social media as an educational and promotional tool rather than as a moderating mechanism. Type of Paper: Empirical Research Paper.